2000
DOI: 10.1258/0022215001906426
|View full text |Cite
|
Sign up to set email alerts
|

Dual infection with atypical mycobacteria and Mycobacterium tuberculosis causing cervical lymphadenopathy in a child

Abstract: The most common presentation of mycobacterial infection encountered in otolaryngological practice is cervical lymphadenitis. We report a child with an unusual cause of cervical lymphadenopathy, i.e. dual tuberculous infections. This had clinical ramifications as, initially Mycobacterium avium-intracellulare was grown in culture and was resistant to standard anti-tuberculous agents, and hence treated with excision of the lymph node. However, the cultures from the excised lymph node grew out Mycobacterium tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Recently, a dual mycobacterial lymphadenitis was described in a pediatric patient [11]. However, we believe that the present case is the first report of associated tubercular and nontubercular mycobacterial bone infection in an immunocompetent host.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, a dual mycobacterial lymphadenitis was described in a pediatric patient [11]. However, we believe that the present case is the first report of associated tubercular and nontubercular mycobacterial bone infection in an immunocompetent host.…”
Section: Discussionmentioning
confidence: 57%
“…Dual infections have been described before and it is suggested that superinfections of previously established granulomas can occur. [18][19][20][21] For another patient a positive culture for M. marinum had originally been obtained but real-time PCR remained repeatedly negative, although it was suitable for the detection of this species. This could be caused by the degrading of DNA, a sensitivity problem or nonhomogenous distribution of the bacteria in the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the culture of excised lymph node grew M. tuberculosis and treatment was modifi ed. [6] Both these cases depended on conventional methodologies like staining and culture, and hence the delay in diagnosis and treatment.…”
Section: Case Reportmentioning
confidence: 99%
“…[5] CHIKV is normally responsible for an acute infection, characterised by high fever, poly-arthralgia, headache and rash. [6] Neurological complications due to CHIKV have been reported from several parts of India. [7] Although in West Bengal the virus had already affected many districts of the state, but to date, no such cases have been reported from this state as well as from Eastern part of India.…”
Section: Introductionmentioning
confidence: 99%